Exposure to deltamethrin affects development of Plasmodium falciparum inside wild pyrethroid resistant Anopheles gambiae s.s. mosquitoes in Uganda - Kristan, Mojca (Parasit Vectors, 2016)
BACKGROUND: Pyrethroid resistance in African vector mosquitoes is a threat to malaria control. Resistant mosquitoes can survive insecticide doses that would normally be lethal. We studied effects of such doses on Plasmodium falciparum development inside kdr-resistant Anopheles gambiae s.s. in Uganda. METHODS: We collected An. gambiae s.s. homozygous for kdr-L1014S mutation, fed them on blood samples from 42 P. falciparum-infected local patients, then exposed them either to nets treated with sub-lethal doses of deltamethrin or to untreated nets. After seven days, we dissected 692 mosquitoes and examined their midguts for oocysts. Prevalence (proportion infected) and intensity of infection (number of oocysts per infected mosquito) were recorded for each group. RESULTS: Both prevalence and intensity of infection were significantly reduced in deltamethrin-exposed mosquitoes, compared to those exposed to untreated nets. With low doses (2.5–5.0 mg/m(2)), prevalence was reduced by 59 % (95 % CI = 22 %-78 %) and intensity by 41 % (95 % CI = 25 %-54 %). With high doses (10–16.7 mg/m(2)), prevalence was reduced by 80 % (95 % CI = 67 %-88 %) and intensity by 34 % (95 % CI = 20 %-46 %). CONCLUSIONS: We showed that, with locally-sampled parasites and mosquitoes, doses of pyrethroids that are sub-lethal for resistant mosquitoes can interfere with parasite development inside mosquitoes. This mechanism could enable pyrethroid-treated nets to prevent malaria transmission despite increasing vector resistance.